KANDIDAT MATERI GELAP DALAM MODEL CERMIN BARU - , Chalis Setyadi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The possibility of dark matter existence from a new mirror model with two particle sectors, namely standard model sector and mirror sector has been studied. It has also been shown that in the mirror sector, there are two particles that can be dark matter candidates which do not interact with standard model sector except by Higgs mixing, are neutral, and do not decay into other particles. These candidates are mirror proton and mirror electron (E). With an asumption that dark matter abundance